Noble Character Building Management at Islamic Education Institution - Nursanti, Ririn (International Conference of Moslem Society, 2018)
We believe that globalization makes an impact on society and cultural transformation phenomena among Muslim youth generation. Moral crisis in school-age teenagers is one of the transformation shapes. Noble-Character building is the most required action to develop a quality and though people. Islamic educational institution shows a crucial part of this unwanted transformation. We believe that this institution can utilize all learning resources to make character building performs optimally. There is a need to find innovative management strategy to develop ready-to-life skills for youth people so they will face globalization era successfully. The research focuses on noble-character building management at Islamic educational institution. We use a descriptive method using a qualitative approach, observation, interviews, and documentary study. We observe the principal, teachers, students, and stakeholders then process the data using qualitative analysis. The result indicates that they need to reformulate noble-character building management through: rearrange vision and mission that should adopt noble-character building, optimize teachers as a role model, create integrated curriculum, develop local values, and involve all stakeholders as strong teamwork.